KEGIATAN CSR PERUSAHAAN: PERSEPSI NASABAH BANK BCA DAN BANK MANDIRI - Antania Shinta Yuwono; Kurniawati , (Media Riset Akuntansi, Auditing & Informasi, 2013)
The background of this research was to determine the attitude of customers in Indonesia on different platforms CSR and CSR initiatives, their responses in order to obtain information about the perception of the company’s CSR activities.This study aims to analyze the perception of consumers towards CSR platform, CSR initiatives and CSR based on strategy marketing. This study used each of the 80 respondents to obtain information about their perceptions of CSR activities of the company. The calculation of the study using SPSS. In this study the analysis of the data used are qualitative and quantitative data. The results of this study both variables CSR Platform bank customers BCA and Bank Mandiri had a positive response, the variable CSR initiatives both bank customers and bank Bank Mandiri has a positive response, and variable Marketing Strategy CSR both bank customers and bank Bank Mandiri had a positive response.